Assessment and improvement of adhesion of printed silver-based inks on alumina produced by fused filament fabrication - Utsch, Daniel; Sippel, Marcel; Voigt, Christian; Häußler, Felix; Franke, Jörg (Power Electronic Devices and Components, 2024)
More efficient electronic systems need more temperature-stable substrate materials and more flexible production possibilities. Ceramics such as alumina can be used for 2D and 3D base bodies, since they provide better thermal properties than their polymeric counterparts and can be additively manufactured utilizing e.g. Fused Filament Fabrication. Proper functionalization can be achieved by applying methods of printed electronics. Here, adhesion of the functional ink to a substrate is a crucial issue and especially challenging on ceramic substrates. This contribution reached a noteworthy increase in this matter, using a modified silver-based ink with piezojet-printing, while preserving very low electrical resistance after convection sintering. Adhesion is determined by pull-off testing, based on ISO 4624. By the approach shown in this work, printed ceramics could become a more viable choice for use in functional electronic systems.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Additive manufacturing; Adhesion; Alumina; Printed electronics; Pull-off testing